Analisis Kinerja Keuangan Lembaga Zakat (Studi Kasus : Badan Amil Zakat Nasional) - Efri Syamsul Bahri; Maya Romantin; Ahmad Tirmidzi Lubis (Universitas Muhammadiyah Sidoarjo, 2017)
National Amil Zakah Board has a big responsibility to hold the trust of government and society to zakah management in Indonesia. The problem is how the financial performance of National Amil Zakah Agency? This study aims to assess the financial performance of zakah institutions by using financial performance measurement ratio model from Ritchie & Kolodinsky (2003) research for non-profit organizations. The object used in this research is the financial report of Badan Amil Zakat Nasional (BAZNAS) during the period 2004 to 2013. The components of the ratio used are five ratio of Ritchie & Kolodinsky model. Based on Ritchie & Kolodinsky ratios, these five ratios show BAZNAS's financial performance over the last decade well expressed.